Bancos digitais X bancos tradicionais: uma análise das implicações causadas pelos bancos digitais no mercado bancário brasileiro - Marques, Frank Borges (2019)
This study aims to analyze the implications of digital transformation, and consequently the emergence of Digital Banks, in the Brazilian banking sector. In order to achieve this goal, five specific objectives were defined, namely: to describe the evolution of customer service channels used in the banking sector from 2011 to 2017; describe the regulatory changes and the evolution of the so-called Digital Banks in Brazil from 2013 to 2019; analyze the implications caused by Digital Banks in the Brazilian banking market; analyze the interactions of Nubank Bank customers reported at NuCommunity; and develop executive summary for submission to Banco Triangulo Management / Board with survey results (available in Appendix A). The research had as theoretical basis the studies on market segmentation and consumer behavior, innovation and technology in the banking sector and Fintechs / Digital Banks. For the construction of the study the qualitative approach was used. The research consisted of two stages, the first descriptive and the second exploratory, using secondary data in documents released by BACEN, FEBRABAN, website of financial institutions and Digital Banks, as well as Facebook. For this, the techniques of document analysis were used. As main results were identified movements of the banking market in order to invest in technologies and processes that allow the maximum digitization of the relationship with customers, the approximation of the marketing and communication lines of traditional banks to those practiced by Digital Banks, correlating their brands to agile and cost-effective digital processes. We also identified 16 regulations issued by BACEN to regulate the action of payment arrangements in Brazil. By analyzing the perception of customers of Nubank through Nu Community it was identified that most customers act as promoters of the brand.